Menantang Paradigma : Citra Tubuh dan Obesitas pada Remaja Akhir di Indonesia - Sokang, Yasinta Astin; Sidharta, Novetania (Universitas Wiralodra, 2024)
The adolescent perspective on body image is influenced by individual experiences and mass media portrayals. Considering society's perception that being thin and having fair skin defines beauty, this research aimed to explore the body image of late adolescents in Indonesia. The researchers hypothesized that adolescents with obesity would have a negative body image, while non-obese adolescents would have a positive body image. The Body Appreciation Scale-2 (BAS-2) was used for measurement. A total of 421 late adolescent respondents (aged 18-21) from various islands in Indonesia participated in the study. The research findings rejected the initial hypothesis. Based on categorization according to Body Mass Index (BMI), respondents categorized as underweight, normal weight, overweight, and obesity type I exhibited high body image categories. Meanwhile, respondents classified as obesity type II had a moderate body image category. These results are discussed in detail in the discussion section.